The efficacy and safety analysis of first-line immune checkpoint inhibitors in pulmonary sarcomatoid carcinoma - Zeng, Zhimin; Qian, Xiaoying; Liu, Fanrong; Wang, Yong; Yuan, Yong; Fang, Chen; Zhang, Xinwei; Yuan, Shangkun; Chen, Renfang; Yu, Biao; Wang, Tong; Yin, Yan; et al. (Frontiers in Immunology, 2022)
Background: Pulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive disease without standardized treatment strategies. The efficacy of second-line or beyond immune checkpoint inhibitors (ICIs) has been proven in recent studies, while the evidence for first-line immunotherapy for PSC is still limited to case reports and remains poorly understood. Materials and methods: This was a multicenter, retrospective analysis of 21 patients with a histological diagnosis of PSC who received ICI as first-line therapy from January 2019 to March 2022. The expression of PD-L1 was evaluated by immunohistochemistry (IHC) using the monoclonal antibody 22C3. Low and high PD-L1 expression were defined using the tumor proportion score (TPS), with cutoffs of 1% and 50%, respectively. Results: All 8 patients had PD-L1 positivity who underwent PD-L1 expression assessment, and 6 patients (6/8, 75.0%) had high PD-L1 expression. Among the 21 PSC patients, 7 received tislelizumab, 6 received camrelizumab, 4 received sintilimab, 3 received pembrolizumab, and 1 received durvalumab. Among them, 18 PSCs received combination therapy, while another 3 PSCs received immunotherapy alone. Twelve out of 21 (57.1%) PSC patients achieved a partial response (PR), and 5 patients had stable disease (SD) as the best response, while 4 PSCs experienced dramatic progressive disease (PD). The median PFS was 9.2 (95% CI 4.3-14.1) months, and the median OS was 22.8 (95% CI 4.0-41.5) months. Among the three treatment groups (immunotherapy alone, immunotherapy combined with anlotinib, and chemo-immunotherapy), the median PFS was 8.0 months, 9.4 months, and 9.6 months, and the median OS was 19.0 months, 22.8 months, and 30.6 months, respectively. There was no difference in PFS and OS between the three treatment regimens groups (P=0.86 and P=0.34, respectively) and different immunotherapies (P=0.10 and P=0.23, respectively). No serious adverse events (grade ≥3) were noted. Conclusion: First-line immunotherapy has promising therapeutic potential in the treatment of PSC. More studies are warranted to confirm these findings.